Association between parasite microbiomes and caste development and colony structure in a social trematode. Issue 21 (2nd September 2022) - Jorge, Fátima; Dheilly, Nolwenn M.; Froissard, Céline; Poulin, Robert
Abstract: Division of labour through the formation of morphologically and functionally distinct castes is a recurring theme in the evolution of animal sociality. The mechanisms driving the differentiation of individuals into distinct castes remain poorly understood, especially for animals forming clonal colonies. We test the association between microbiomes and caste formation within the social trematode Philophthalmus attenuatus, using a metabarcoding approach targeting the bacterial 16S SSU rRNA gene. Clonal colonies of this trematode within snail hosts comprise large reproductive individuals which produce dispersal stages, and small, non‐reproducing soldiers which defend the colony against invaders. In colonies extracted directly from field‐collected snails, reproductives harboured more diverse bacterial communities than soldiers, and reproductives and soldiers harboured distinct bacterial communities, at all taxonomic levels considered. No single bacterial taxon showed high enough prevalence in either soldiers or reproductives to be singled out as a key driver, indicating that the whole microbial community contributes to these differences. Other colonies were experimentally exposed to antibiotics to alter their bacterial communities, and sampled shortly after treatment and weeks later after allowing for turnover of colony members. At those time points, bacterial communities of the two castes still differed across all antibiotic treatments; however, the caste ratio within colonies changed: after antibiotic disruption and turnover of individuals, new individuals were more likely to become reproductives than in undisturbed control colonies. Our results reveal that each caste has a distinct microbiome; whether the social context affects the microbiota, or whether microbes contribute to modulating the phenotype of individuals, remains to be determined.